ByzRev 07.2025.008: David Holton – Geoffrey Horrocks – Marjolijne Janssen – Tina Lendari – Io Manolessou – Notis Toufexis, The Cambridge Grammar of Medieval and Early Modern Greek in 4 vols.: Cambridge: Cambridge University Press 2019. - Kisilier, Maxim (The Byzantine Review, 2025)
David Holton – Geoffrey Horrocks – Marjolijne Janssen – Tina Lendari – Io Manolessou – Notis Toufexis, The Cambridge Grammar of Medieval and Early Modern Greek in 4 vols. Cambridge: Cambridge University Press 2019. 2024 pp. – ISBN 978-0-521-19529-4